Fracture characteristics of fibre reinforced composite bars used to provide rigid orthodontic dental segments - Tahmasbi Soodeh; Heravi Farzin; Moazzami Saied Mostafa (Sciendo, 2023)
Fibre reinforced composites (FRC) can be used to join teeth as a rigid unit for anchorage purposes and/or for tooth movement. The utility of FRCs for these applications depends on the fracture characteristics and durability of the material under masticatory loads.